The enigma of the oceanic feeling : revisioning the psychoanalytic theory of mysticism - Parsons, William Barclay, 1955- (Oxford University Press, 1999)
This study examines the history of the psychoanalytic theory of mysticism, starting with the seminal correspondence between Freud and Romain Rolland concerning the concept of "oceanic feeling." Providing a corrective to current views which frame psychoanalysis as pathologizing mysticism, Parsons reveals the existence of three models entertained by Freud and Rolland: the classical reductive, ego-adaptive, and transformational (which allows for a transcendent dimension to mysticism). Then, reconstructing Rolland's personal mysticism (the "oceanic feeling") through texts and leaf